Academic Integrity in the Context of European Experience and Ukrainian Practice - Anastasiia Dorozhko (Educational Challenges)
The article analyses the experience of European countries in counteraction to academic dishonesty and plagiarism, as well as the attitude of Ukrainian students to the problem. The specific examples of the counteraction against academic fraud in universities abroad have been studied, in particular, in the United Kingdom at the University College London, in Sweden at the Karolinska Medical University, and in higher education institutions in Poland. The article examines the attitude of Ukrainian students to various issues of academic integrity by questionnaires for its development in higher education institutions to prevent plagiarism in Master's theses.